BASE PRINCIPLES OF MULTIMEDIA EDUCATIONAL MOBILE APPLICATIONS PLANNING - Bilous, Vladyslav (Educological discourse, 2019)
Base principles of educational mobile educational applications planning are presented in the article. Educating with the active use of informatively-communication technologies in the future will be closely related to the development and distribution of mobile communication, on-line tutorials and appendixes means, use of technology of gesticulation interfaces, which quality of education will allow to promote and to extend the possibilities. It’s marked that in spite of wide distribution and availability of mobile devices among students, the mobile educating is poorly widespread in educational establishments. Founding a new infomedia serves, and changing approaches in education would become an appropriate solution. There is a constant change requirement to one or another educational mobile technology. New principles of teaching applications planning are required, firstly in prototyping. The description to the concept "mobile education" is given. Possibilities of intensification of educating and increase of motivation are examined by means of modern multimedia technologies. The stages of mobile teaching application construction are described. Recommendations are given for creation of the program not only for the European countries but also for the whole world. Similarly, from examples the attributes of creation are considered for the Arabic countries, where the written language differs from European and the principle localization both for a country and for separate regions. Experience is analysed from the study of mobile education. A review is given on creation of layouts under different screens among that are smartphones, tablets, PDA. Programming languages are presented for each of devices. Distinguished technical features of the use of smartphones. The conclusion show, that most modern students are technically and psychologically ready to use mobile technologies in education, and it is necessary to examine new possibilities for more effective use of potential of the mobile educating. Base principles of planning are offered to the review for mobile educational applications.